Efficacy and Tolerability of Repetitive Transcranial Magnetic Stimulation on Suicidal Ideation: A Systemic Review and Meta-Analysis - Chen, Guan-Wei; Hsu, Tien-Wei; Ching, Pao-Yuan; Pan, Chih-Chuan; Chou, Po-Han; Chu, Che-Sheng (Frontiers in Psychiatry, 2022)
Objective: This study aimed to investigate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in treating suicidal ideation in patients with mental illness. Method: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Major electronic databases were systematically searched from the time of their inception until July 22, 2021. The primary outcome was the mean change in the scores for suicidal ideation. The secondary outcome was the mean change in depression severity. Results: Ten randomized controlled trials were eligible with 415 participants in the active treatment group (mean age = 53.78 years; mean proportion of women = 54.5%) and 387 participants in the control group (mean age = 55.52 years; mean proportion of women = 51.78%). rTMS significantly reduced suicidal ideation (k = 10, n = 802, Hedges' g = −0.390, 95% confidence interval [CI] = −0.193 to −0.588, p < .001) and severity of depressive symptoms (k = 9, n = 761, Hedges' g = −0.698, 95% CI = −1.023 to −0.372, p < 0.001) in patients with major mental disorders. In the subgroup analysis, rTMS reduced suicidal ideation among patients with non-treatment-resistant depression (non-TRD) (-0.208) but not in those with TRD. rTMS as combination therapy had a larger effect than did monotherapy (-0.500 vs. -0.210). Suicidal ideation significantly reduced in patients receiving more than ten treatment sessions (-0.255). Importantly, the rTMS group showed favorable tolerability without major adverse events. Conclusion: The study showed that rTMS was effective and well-tolerated in reducing suicidal ideation and depression severity in patients with major mental disorders.